Pharmacokinetics, safety and tolerability of intravenous ferric carboxymaltose: a dose-escalation study in volunteers with mild iron-deficiency anaemia - Geisser, Peter; Banké-Bochita, José (Arzneimittelforschung, 2010)
Iron-deficiency anaemia (IDA) represents a major burden to public health worldwide. The therapeutic aim for patients with IDA is to return iron stores and haemoglobin (Hb) levels to within the normal range using supplemental iron therapy and erythropoiesis-stimulating agents. Oral and previous intravenous (i. v.) iron formulations have a number of disadvantages, including immunogenic reactions, oxidative stress, low dosages, long administration times and the requirement for a test dose. Ferric carboxymaltose (FCM, Ferinject®) is a novel, next-generation i. v. iron formulation with the potential to overcome these limitations. In this single-centre, randomized, double-blind, placebo-controlled study, the pharmacokinetics (PK), pharmacodynamics (PD), safety and tolerability of single, escalating doses of FCM were investigated.Four ascending doses were investigated in a total of 24 patients with mild IDA (defined as serum ferritin < 20 µg/l and transferrin saturation [TfS] < 16%): 100 mg iron as FCM given as an i. v. bolus injection, and 500, 800 and 1000 mg iron as FCM given as an i. v. infusion over 15 min. At each dose level six patients received FCM and two received placebo. The decision to escalate to the next dose was based on evaluation of safety and tolerability data from the previous dose. The maximum duration of the study was 5 weeks from screening to final assessment. Assessments were made of PK iron-status parameters up to 168 h post-dose. Safety assessments included incidence of adverse events (AEs), clinical laboratory parameters and vital signs. PK and PD parameters were analysed using descriptive statistics. All analyses were performed on the safety population, which included all patients who received ≥ 1 dose of study medication.Seventy-seven patients were screened and, of these, 32 male and female patients with pre-study Hb between 9.2 and 11.9 g/dl and serum ferritin < 20 µg/l were included in the study. Two patients had TfS > 16% (19.2% and 17.2%); both patients were considered by the investigator to be eligible for inclusion. Compared with placebo, a rapid, dose-dependent increase in total serum iron was observed across all dose groups. Mean (standard deviation) maximum total serum iron levels ranged between 36.9 (4.4) and 317.9 (42.3) µg/ml in the 100 and 1000 mg groups. Concentration–time curves of total serum iron continuously declined for up to 24 and 72 h post-dose in the 100 and 500–1000 mg groups, respectively. Non-compartmental analysis of PK parameters was truncated at 24 h (100 mg) and 72 h (500–1000 mg doses). A dose-dependent, but not dose-linear, increase in serum ferritin was seen in all treatment groups compared with placebo, with peak levels of a 23–210-fold increase above baseline occurring 48–120 h postdose. Iron-binding capacity was transiently almost fully utilized after doses of 500, 800 and 1000 mg (TfS > 95%). No meaningful changes in serum transferrin or serum transferrin receptor concentrations were observed during this study. The elimination pattern for FCM appeared to be mono-exponential; FCM was cleared from serum with a terminal half-life of approximately 7.4–12.1 h. The percentage of FCM excreted in urine was negligible (0.0005%). FCM was well tolerated; a total of 19 AEs were reported by 8/32 patients (25%), of which three were considered by the investigator to be related to FCM: nausea and vomiting (one patient [100 mg]), and headache (one patient [1000 mg]). The incidence of AEs did not increase with dose. No severe or serious AEs, or deaths occurred. FCM had no significant effect on laboratory safety parameters or vital signs.This study satisfactorily characterized the PK/PD parameters of single doses of 100, 500, 800 and 1000 mg iron as FCM. The majority of FCM was utilized or eliminated within 24 h of administration of a 100 mg dose and within 72 h of a 500 −1000 mg dose. FCM was generally well tolerated across all doses in patients with mild IDA.
Keywords: Anaemia; Ferinject®; Ferric carboxymaltose, pharmacodynamics, pharmacokinetics; Intravenous iron; Iron deficiency